PENINGKATAN KETERAMPILAN BERBICARA MELALUI KEGIATAN DISKUSI KELOMPOK DENGAN TEKNIK PROBING PROMPTING PADA SISWA KELAS X SMA NEGERI 3 MAKASSAR - Abu Bakar Tumpu; Herawati Arief S (AIJER: Algazali International Journal Of Educational Research, 2020)
Abstract. Improving Speaking Skills through Group Discussion Activities with Probing Prompting Techniques for Class X Students of SMA Negeri 3 Makassar. This study aims to improve speaking skills through group discussion activities with the probing prompting technique for class X.2 students of SMA Negeri 3 Makassar. This type of research is a class action research (class action reaserch) which consists of 2 cycles where each cycle is carried out only two meetings. Research procedures include planning, implementing, observing and reflecting. The subjects in this study were 33 students of class X.2 SMA Negeri 3 Makassar. The data collection techniques used in this study were: tests, observation sheets and documentation. The results showed that there was an increase in speaking skills through group discussion activities with the probing prompting technique in class X.2 SMA Negeri 3 Makassar in giving the test cycle I obtained an average score of 72.06 with a percentage of 73% and increased in the second cycle 79 test. , 93 with a percentage of 80.0%. Learning Indonesian using probing prompting learning techniques can improve students' speaking skills.